Punish ability and Punishment for Careless Transport Crimes - BAKISHEV, Kairat A.; KHANOV, Talgat A.; NURGALIEV, Bahit M.; ABDRAHMANOV, Daniyar S. (Journal of Advanced Research in Law and Economics, 2019)
The main purpose of this study is to analyze the system of punishment for transport crimes and make proposals for its improvement. According to the Concept of the Legal Policy of Kazakhstan for the period from 2010 to 2020, the Criminal Code 2014 should continue the policy of humanization of responsibility for persons who have committed careless crimes, including transport crimes, to expand the scope of application of criminal penalties not related to imprisonment, establishing the proportionality of punishment in the sanctions of articles of the Criminal Code, etc. However, these guidelines have not been fully implemented. The analyses of the road traffic criminal infractions system showed that legislators made some mistakes. The study points out that the sanctions of articles of the system are excessively overstated or unreasonably understated or have unjustifiably large intervals between the upper and lower limits, and therefore do not fully correspond to the nature and degree of social danger of these crimes. In this regard, the authors formulated proposals for improvement of the system of punishment for transport criminal infractions: to reduce the term of punishment in the form of imprisonment for transport crimes provided by Art. 344, 345, 346, 358, 360 of the Criminal Code from ten years down to seven or eight years; to expand the sanctions of the relevant articles by including penalties not related to imprisonment - fine, corrective labor, restriction of liberty, to amend Art. 46 of the Criminal Code. To solve this problem, the study used theoretical and empirical scientific methods: theory, analysis, deduction and synthesis, research and measurement, experiment, as well as historical, logical, comparative-historical, retrospective and statistical methods.